Dietary fat intake and risk of stroke in male US healthcare professionals: 14 year prospective cohort study. Issue 7418 (2nd October 2003) - He, Ka; Merchant, Anwar; Rimm, Eric B; Rosner, Bernard A; Stampfer, Meir J; Willett, Walter C; Ascherio, Alberto
Abstract: Objective To examine the association between intake of total fat, specific types of fat, and cholesterol and risk of stroke in men. Design and setting Health professional follow up study with 14 year follow up. Participants 43 732 men aged 40–75 years who were free from cardiovascular diseases and diabetes in 1986. Main outcome measure Relative risk of ischaemic and haemorrhagic stroke according to intake of total fat, cholesterol, and specific types of fat. Results During the 14 year follow up 725 cases of stroke occurred, including 455 ischaemic strokes, 125 haemorrhagic stokes, and 145 strokes of unknown type. After adjustment for age, smoking, and other potential confounders, no evidence was found that the amount or type of dietary fat affects the risk of developing ischaemic or haemorrhagic stroke. Comparing the highest fifth of intake with the lowest fifth, the multivariate relative risk of ischaemic stroke was 0.91 (95% confidence interval 0.65 to 1.28; P for trend = 0.77) for total fat, 1.20 (0.84 to 1.70; P = 0.47) for animal fat, 1.07 (0.77 to 1.47; P = 0.66) for vegetable fat, 1.16 (0.81 to 1.65; P = 0.59) for saturated fat, 0.91 (0.65 to 1.28; P = 0.83) for monounsaturated fat, 0.88 (0.64 to 1.21; P = 0.25) for polyunsaturated fat, 0.87 (0.62 to 1.22; P = 0.42) for trans unsaturated fat, and 1.02 (0.75 to 1.39; P = 0.99) for dietary cholesterol. Intakes of red meats, high fat dairy products, nuts, and eggs were also not appreciably related to risk of stroke. Conclusions These findings do not support associations between intake of total fat, cholesterol, or specific types of fat and risk of stroke in men.